Connecting Big Data and Service Quality Evaluation – Developing a Service Quality Map of the Austrian Hospitality Industry through the Application of Big Data (The Gaze: Journal of Tourism and Hospitality, 2017)
The impact of online reviews on guests, hotel owners and other parties is growing in importance. In reference to online reviews, service quality plays a crucial role in hotel diff erentiation and influencing the choice of accommodation made by travellers. Thus, online reviews represent a valuable source of information about perceived service, that has not been fully exploited yet. This research paper attempts to look more closely at this extensive body of data. The authors have conceptualized a tool that assists governmental institutions, DMOs and investors in decision making. This tool accumulates intelligent data and provides a comprehensive overview of the Austrian hospitality industry and its service quality standards. It allows the user to conduct specific queries on how a certain dimension of service quality is perceived. The results can be either visualized on a density map or extracted as a structured .csv file for further analysis.The GAZE Journal of Tourism and Hospitality Vol. 8, 2017, page: 40-54